5z=-3(z+8)

Simple and best practice solution for 5z=-3(z+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z=-3(z+8) equation:


5z=-3(z+8)

We simplify the equation to the form, which is simple to understand
5z=-3(z+8)

Reorder the terms in parentheses
5z=+(-3z-24)

Remove unnecessary parentheses
+5z=-3z-24

We move all terms containing z to the left and all other terms to the right.
+5z+3z=-24

We simplify left and right side of the equation.
+8z=-24

We divide both sides of the equation by 8 to get z.
z=-3

See similar equations:

| 3x+9=7x-9 | | -1[a-1(a+-5)]+-3=-5-1(-9+-5) | | 5c=-3(2+8) | | 12(3x+6)-7(2x-6)=2x-26 | | 2(3x-6)=3(x-9) | | 14x-1-5x=-28+12x | | 3x-4(2x+2)=2 | | 8w-10= | | -x+6=-30 | | 5x+12=102 | | 5x=-1.8 | | 6x^2-7=10 | | 7u=4 | | -4x-4=6-3x | | 7x+4=5x+17 | | v-18=3v-7+3 | | a=b-4c | | 4+11s-2=6s+10-3s | | 8y-y=6 | | 8z-48=-16 | | -[a-(a-5)]-3=-5-(-9-5) | | 63=-2x-5x+7 | | 17+b=b-4+7b | | 8+15h-1=8h+79-4h | | 2-3a=4+a | | 4x-17(1-x)=42 | | -8(k-7)-(5+2k)=-11k | | 7x-8=3x+22 | | 2x-a=x-b | | 3x+4=-5x+12 | | -1=-7x-7(-2x-10) | | 6-4x=6x+8x+10 |

Equations solver categories